EKSPERIMENTAL MEKANIKA GERAK KINCIA PADA KARYA SENI KINETIK - Kiram, M Fauzul; Bahrudin, Ahmad; Nofrial, Nofrial (Institut Seni Indonesia Padangpanjang, 2023)
Kincia is one of the cultural products in Minangkabau that functions as a tool for pounding rice by utilizing the power of river water flow. The concept of creation is inspired by traditional technology and cultural values that exist in kincia in Minangkabau, the concept and idea of this creation are realized using the theoretical basis of form, function, aesthetic, and kinetic. The creation of this work goes through several stages, namely exploration, design, and realization In the process of working on this work using craft techniques, namely scroll techniques, lathe techniques, construction techniques and lamination techniques, the materials used in making this work are several types of wood such as Surian wood, jackfruit wood, jelutung wood, and rengas wood. created using a power source from the rotation of the lever which is allowed for direct movement by the audience and some works using a rotating motor such as a dynamo, some works highlight interaction with the audience to provide a different experience that will be felt by the audience. Kincia adalah salah satu produk kebudayaan di Minangkabau yang berfunfgsi sebagai alat untuk menumbuk padi dengan memanfaatkan tenaga aliran air sungai. Konsep penciptaan ini terinspirasi dari teknologi tradisional dan nilai-nilai budaya yang ada pada kincia di Minangkabau, konsep dan ide penciptaan ini diwujudkan mengunakan landasan teori bentuk, fungsi, estetis, dan kinetic, Penciptaan karya ini melewati beberapa tahapan yaitu eksplorasi, perancangan, dan perwujudan, dalam proses pengerjaan karya ini memakai teknik kriya yaitu teknik scroll, teknik bubut, teknik kontruksi dan teknik laminasi, bahan yang digunakan dalam pembuatan karya ini adalah beberapa jenis kayu seperti kayu surian, kayu nangka, kayu jelutung, dan kayu rengas, karya yang di ciptakan mengunakan sumber tenaga dari putaran tuas yang di perbolehkan untuk gerakan langsung oleh penikmat dan beberapa karya menggunakan motor putar sepeti dinamo, beberapa karya menonjolkan interaksi dengan penikmat untuk memberikan pengalaman berbeda yang akan dirasakan penikmat.